Therapeutic and immune-regulation effects of Scutellaria baicalensis Georgi polysaccharide on pseudorabies in piglets - Shu, Xianghua; Zhang, Ying; Zhang, Xue; Zhang, Ying; Shu, Yue; Wang, Yulei; Zhang, Zhihui; Song, Chunlian (Frontiers in Veterinary Science, 2024)
Pseudorabies virus (PRV) can cause fatal encephalitis in newborn pigs and escape the immune system. While there is currently no effective treatment for PRV, Scutellaria baicalensis Georgi polysaccharides (SGP) and Rodgersia sambucifolia Hemsl flavonoids (RHF) are traditional Chinese herbal medicines with potential preventive and therapeutic effects against PRV infection. In order to explore which one is more effective in the prevention and treatment of PRV infection in piglets. We investigate the therapeutic effects of RHF and SGP in PRV-infected piglets using clinical symptom and pathological injury scoring systems. The immune regulatory effects of RHF and SGP on T lymphocyte transformation rate, cytokines, T cells, and Toll-like receptors were also measured to examine the molecular mechanisms of these effects. The results showed that SGP significantly reduced clinical symptoms and pathological damage in the lungs, liver, spleen, and kidneys in PRV-infected piglets and the T lymphocyte conversion rate in the SGP group was significantly higher than that in the other treatment groups, this potential dose-dependent effect of SGP on T lymphocyte conversation. Serum immunoglobulin and cytokine levels in the SGP group fluctuated during the treatment period, with SGP treatment showing better therapeutic and immunomodulatory effects in PRV-infected piglets than RHF or the combined SGP+RHF treatment. In conclusion, RHF and SGP treatments alleviate the clinical symptoms of PRV infection in piglets, and the immunomodulatory effect of SGP treatment was better than that of the RHF and a combination of both treatments. This study provides evidence for SGP in controlling PRV infection in piglets.